Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bạn xem lại đề câu a) cho rõ lại
Câu b) Tại x=2013 thì B=x2013-(x+1)x2012+(x+1)x2011-(x+1)x2010+...-(x+1)x2+(x+1)x-1
= x2013-x2013-x2012+x2012+x2011-x2011-x2010+..-x3 - x2+x2+x-1
= x-1 = 2012
![](https://rs.olm.vn/images/avt/0.png?1311)
x = 2013 => x + 1 = 2014
Ta có:\(B=x^{2013}-2014x^{2012}+2014x^{2011}-2014x^{2010}+...+2014x-1\)
\(=x^{2013}-\left(x+1\right)x^{2012}+\left(x+1\right)x^{2011}-\left(x+1\right)x^{2010}+...+\left(x+1\right)x-1\)
\(=x^{2013}-x^{2013}-x^{2012}+x^{2012}+x^{2011}-x^{2011}-x^{2010}+...+x^2+x-1\)
\(=x-1\)
\(=2013-1\)
\(=2012\)
\(X=2013\Rightarrow2014=X+1\Rightarrow B=X^{2013}-\left(X+1\right)\times X^{2012}+...+\left(X+1\right)\times X-1\)\(X-1\)
\(\Rightarrow B=X^{2013}-X^{2013}-X^{2012}+...+X^2+X-1\)
\(\Rightarrow B=X-1\)\(=2013-1=2012\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1. A = 75(42004 + 42003 +...+ 42 + 4 + 1) + 25
A = 25 . [3 . (42004 + 42003 +...+ 42 + 4 + 1) + 1]
A = 25 . (3 . 42004 + 3 . 42003 +...+ 3 . 42 + 3 . 4 + 3 + 1)
A = 25 . (3 . 42004 + 3 . 42003 +...+ 3 . 42 + 3 . 4 + 4)
A = 25 . 4 . (3 . 42003 + 3 . 42002 +...+ 3 . 4 + 3 + 1)
A =100 . (3 . 42003 + 3 . 42002 +...+ 3 . 4 + 3 + 1) \(⋮\) 100
![](https://rs.olm.vn/images/avt/0.png?1311)
=>\(-B=\left(1-\frac{1}{2}\right)\left(1-\frac{1}{3}\right)...\left(1-\frac{1}{2012}\right)\)
=\(\frac{1}{2}.\frac{2}{3}...\frac{2011}{2012}=\frac{1}{2012}\)
![](https://rs.olm.vn/images/avt/0.png?1311)